Pengaruh Historisitas Terhadap Perbedaan Kajian Al-Qur’an Barat dan Timur: Studi Analisis Historis - Qudus Al Faruq, Abdul; Fuadi, Muhammad Azhar; Mubarok, Mubarok (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
This research explores the differences in approaches to Qur'anic studies between the East and the West, focusing on the impact of historical contexts on the development of methodologies in both regions. In the East, Qur'anic studies are generally normative and rooted in established Islamic traditions, emphasizing spirituality and Islamic law. In contrast, Western approaches are more critical and analytical, employing historical, hermeneutic, and philological methodologies to understand the Qur'an within historical, sociological, and linguistic contexts. This study utilizes a historical analysis method to identify how historical, cultural, and academic traditions influence these differences. Data were collected through literature reviews from various relevant sources, including books, journals, and scholarly articles. The findings indicate that the historical contexts between the East and the West play a significant role in shaping the methods and understanding of Qur'anic studies. In the West, the focus on critical approaches often overlooks spiritual aspects, while in the East, the emphasis on tradition and religious authority tends to limit critical analysis. The research concludes that these different approaches have their respective strengths and weaknesses and that dialogue between these two traditions can enrich global understanding of the Qur'an. This study highlights the importance of considering historical and cultural backgrounds when developing more comprehensive and inclusive methodologies for Qur'anic studies.